Nina Stibbe: Love, Nina. Despatches from Family Life - Jaine, Tom (Petits Propos Culinaires, 2014)
Nina Stibbe: Love, Nina. Despatches from Family Life: Penguin-Viking, 2013: 322 pp., hardback, £12.99.